Induced production of α-tocotrienol by co-suppression of tocopherol cyclase gene in vegetable crops - Munusamy, Umaiyal; Abdullah, Siti Nor Akmar; Abdul Aziz, Maheran; Khaza'ai, Huzwah; Lai, Mun Seong (Science Publications, 2013)
This study involves the induced production of α-tocotrienol by the co-suppression of tocopherol cyclase gene. The Tocopherol/tocotrienol Cyclase (TC) is a key enzyme involved in the biosynthesis of α-tocotrienol. The partial conserved cDNA of TC gene isolated from the oil palm (Elaeis guineensis) that shared greater than 75% sequence identity with TC sequences from other plant species was used to silence TC gene expression in Amaranthus sp. and Allium porrum leaves by co-suppression strategies. This was carried out using recombinant vector constructs designated as p4a11 and p4c9 containing TC driven by the maize Ubiquitin promoter (Ubi1P) and the oil palm leaf-specific promoter (LHCB), respectively. In the Amaranthus sp. leaves infiltrated with p4a11, the α-tocopherol suppression was 85.0, 71.0 and 74.0% on day three, five and seven, respectively and complete suppression was observed in the leaves infiltrated with p4c9. Whereas, only 11.0, 7.0 and 29.0% suppression was detected in Allium porrum leaves infiltrated with p4a11 and 45.0, 4.0 and 57.0% of suppression was observed in Allium porrum infiltrated with p4c9 on day three, five and seven, respectively. Silencing of TC gene driven by LHCB (p4c9) causes the reduction of α-tocopherol production better than by Ubi1P (p4a11). The results have demonstrated that gene silencing through co-suppression is capable of producing α-tocotrienol. However, there is no correlation between the α-tocotrienol production and the α-tocopherol suppression. It has been suggested that the transgene mediated co-suppression mechanism had triggered the vitamin E biosynthesis metabolic pathway to shift towards producing α-tocotrienol.